2018
DOI: 10.1186/s13063-017-2339-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of persistent allergic rhinitis via acupuncture at the sphenopalatine acupoint: a randomized controlled trial

Abstract: BackgroundAllergic rhinitis is a common respiratory disease. Acupuncture is used to treat it in traditional Chinese medicine, and generally, the L120, ST2 and ST36 acupoints are selected in clinical practice. We report a new method of acupuncture at the sphenopalatine acupoint (SPA) for treatment of persistent allergic rhinitis (PAR). The effect of this treatment was investigated using two different needling depths. The efficacy of this treatment was associated with accurate stimulation of the sphenopalatine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 20 publications
0
45
0
Order By: Relevance
“…Sinomenine is one monomer of Chinese traditional herbs and may possess anti-inflammation, anti-oxidation and anti-apoptosis effects (10). Acupuncture is an important therapy used in complementary and alternative medicine, and may exert anti-inflammatory effects (11). Acupuncture targets specific acupoints to improve the body microenvironment and thus effectively treat certain diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Sinomenine is one monomer of Chinese traditional herbs and may possess anti-inflammation, anti-oxidation and anti-apoptosis effects (10). Acupuncture is an important therapy used in complementary and alternative medicine, and may exert anti-inflammatory effects (11). Acupuncture targets specific acupoints to improve the body microenvironment and thus effectively treat certain diseases (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the excluded articles were in Chinese‐language journals, and these included 5 randomized controlled trials (RCTs) . Of the 38 English‐language articles, there were 15 RCTs . Included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of all studied non‐allopathic treatments, acupuncture had the most data to support its use. Fifteen RCTs were present that showed acupuncture to be a useful adjunct to allopathic standard of care as well as being a useful standalone treatment modality for AR . A 2015 English‐language review of both the English and Chinese language literature found 18 RCTs, which highlights the fact that a large portion of the CAM literature is in the non‐English literature .…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis is a chronic respiratory disease with significant health and psychological burden to patients due to the prolonged disease course [13]. In Sri Lanka, also several people seeking treatments for allergic rhinitis from Ayurvedic hospitals.…”
Section: Discussionmentioning
confidence: 99%